Kuhuang alleviates liver fibrosis by modulating gut microbiota-mediated hepatic IFN signaling and bile acid synthesis - Shen, Bo; Zhou, Cui; Gu, Tianyi; Shen, Zhenyang; Guo, Yuecheng; Dai, Weiming; Liu, Yang; Zhang, Jie; Lu, Lungen; Dong, Hui (Frontiers in Pharmacology, 2022)
Background Liver fibrosis is a common pathological progress of chronic liver diseases, while no specific and effective therapeutic agent has been approved for its treatment. We aimed to investigate the effect of Kuhuang on liver fibrosis and its potential mechanism. Materials and methods To induce hepatic fibrosis, either 3,5-diethoxycarbonyl-1,4-dihydro-collidine (DDC) diet was fed or bile duct ligation (BDL) surgery was performed in C57BL/6 mice. Mice were orally administrated with Kuhuang for 7 days before and after BDL respectively, or for 4 weeks along with DDC diet. The assays of hematoxylin and eosin (H&E), Sirius red staining and immunohistology were performed to evaluate hepatic pathology. Hepatic interferon-β (IFN-β) was detected by enzyme-linked immunosorbent (ELISA). RNA sequencing (RNA-seq) was carried out to examine the gene expression profiles of liver tissues, while the mRNA expression of inflammatory, profibrotic, and BA-related genes were further validated by quantitative real-time RT-PCR (qRT-PCR). Hepatic bile acid (BA) alteration was determined by targeted metabolomics assay. The composition of gut microbiota was determined by 16S rRNA sequencing. Results The treatment of Kuhuang attenuated liver fibrosis and reduced inflammatory response in BDL and DDC mice model. Besides, hepatic IFN signaling pathway was activated upon Kuhuang treatment. Kuhuang treatment also significantly decreased the hepatic level of both primary BAs and secondary BAs. In addition, Kuhuang treatment altered gut microbiota composition, with increased abundance of interferon-producing Akkermansia and decreased abundance of bile salt hydrolase (BSH)-producing Lactobacillus, Clostridium and Bifidobacterium. Furthermore, the abundance of Akkermansia was positively correlated to the hepatic mRNA expression of Ifna4 and Ifnb, Isg15 while that of Lactobacillus, Clostridium-sensu-stricto-1 and Bifidobacterium were positively correlated with BA synthesis-related genes. Conclusion Our results suggested that Kuhuang played a protective role in the procession of liver fibrosis, probably through altering the composition of gut microbiota which consequently activate interferon signaling and inhibit bile acid synthesis in the liver.